Witness Position in Court and How to Judge According to Ibnu Rusyd (Reinterpretation in the Book of Bidayatul Mujtahid Wa Nihayatul Muqtasid) - Deni Mulyadi (Al Mashaadir : Jurnal Ilmu Syariah, 2022)
The position of witnesses in court has a fairly important role as evidence if other evidence is not available to provide information about an incident/dispute. In the texts of fiqh books, the matter of witnessing in court is required to be male except for witnesses related to property rights (huquq al-amwal) or body rights. As if women's rights are not recognized when compared to men, this means that there is a gap between fiqh texts and the reality of society. According to Ibn Rushd, the fuqaha agree that when a judge wants to try a case (case trial), the principle of equality must apply between the accuser (prosecutor) and the defendant, or between the applicant and the respondent in a trial court. According to Ibn Rushd, a judge should not only listen to the words of one party without paying attention and listening to the statements of the other party. In this case, Ibn Rushd emphasized that the judge in the trial court must give time and opportunity to the plaintiff to first provide a statement of his indictment after being asked by the judge. If any part of the indictment case or object of the lawsuit which is denied, is rejected by the defendant, then according to Ibn Rushd, the judge must ask and investigate the evidence to the plaintiff. On the other hand, if the plaintiff does not have evidence and the case is related to assets, then based on the agreement of the fuqaha, the defendant must take an oath.